WIMP searches with cryogenic detectors - Kraus, H (2001)
The existence of dark matter in the Universe is well established and various techniques are applied to either directly or indirectly detect this dark matter. Supersymmetry provides a well-motivated candidate, the WIMP, which many direct searches seek to detect. Some of the present dark matter experiments use cryogenic detectors, operating in the mini-Kelvin temperature range. This article introduces the general concept underlying these detectors, discusses the different types of detectors in use and shows how some of the experiments achieve suppression of background by being able to distinguish between nuclear recoil and electron recoil.